GSM teletraffic quality engineering software development/ Suhaili Ahmad Suhaimi - Ahmad Suhaimi, Suhaili (1997)
The objective of this work is to know the performance of Global System , Traffic Measurement and the Quality of the Traffic Engineering for Mobfle Communication telephone network . The performance involve in the service performance , system capacity & die quality of the teletraffic engineering . This projects win describe the how to measure die telephone traffic , analyze & quality of the traffic engineering. Telecommunications networks, like a roads, are said to cany' traffic *, consisting not of vehicles but of telephone caDs or data messages . The more traffic mere is , the more circuits A exchanges must be provided . If traffic exceeds the design capacity then will be pockets of congestion. Short of providing an infinite number of lines , it is impossibes to know in advance precisely how much equipment to build into a telecommunications network so as to meet demands witout congestion . The quality of the teletraffic engineering is important to make sure the service to the custurmer for more efficiency to the future development. To achieve the quality more effiency , I have developed one programming using language QBASIC for quality of the service for Teletraffic Department Celcom (M) Sdn Bhd .